Penerapan Metode Regresi Linear Pada Sistem Peringatan Dini Banjir Berbasis Internet of Things (IoT) - Nugra Zurus Pratama; Tedy Rismawan; Suhardi Suhardi (JURIKOM (Jurnal Riset Komputer), 2022)
Flood is an event when water inundates an area that is usually not flooded for a certain period of time. Floods usually occur because of continuous rainfall and result in overflow of river. Floods can cause negative impact such as puddles of water that enter homes of those affected. Therefore, we need a system to monitor the weather and can provide flood early warning. In this study the weather monitoring system and flood early warning were made based on internet of things by applying linear regression methods. The system consists of a weather sensor node, a water level sensor node and software in the form of a website. The system measures rainfall, air temperature, humidity, and water level. The process of sending data from the sensor to the server uses ESP32 as a microcontroller which is connected to a wifi network and internet. The system will send a notification if the water level is above the normal level. Based on the test results obtained as many as 45 occurrences of rainfall. The percentage of success in predicting water levels using the linear regression method is 94,4% with an error value of 5,6%.